Networks and Economic life - У Пауэлл; Л Смит-Дор (Journal of Economic Sociology, 2010)
This paper gives a critical review of the four main research lines in network analysis. Authors begin with the discussion of an informal aspect of the networks – the role of the social ties in job search, mobilization of collective action and information transferring. After that the authors turn to the analysis of the more developed and formal direction of the network analysis, devoted to the networks and power. The next step is the consideration of the de-evolution of the big vertically centralized integrated firm and its division in complicated relation networks. Finally the paper deals with production networks where the authors underline the importance of space decentralized joined production in the development of new production processes and commercialization of new products. The paper focuses on the studies that demonstrated the main role of the networks in economic life and those studies that complement to each other.